Hansenula anomala versus Meyerozyma guilliermondii in inhibition of Enterobacteriaceae and evaluation of maize storages in Cameroon - Hedman, Oleana (SLU/Dept. of Microbiology, 2011)
In sub-Saharan Africa post-harvest losses constitute a major problem. In order to preserve food and feed in a safe and sustainable way new methods need to be investigated and introduced. One system to preserve grain in a secure and energy saving way is by using a biocontrol organism. The yeast strain Hansenula anomala J121 is known to inhibit growth of moulds and bacteria from the Enterobacteriaceae family in stored cereal grain and is therefore regarded as a biocontrol organism.